STUDI VALIDITAS DAN REALIBILITAS FAKTOR SUKSES IMPLEMENTASI E-GOVERNMENT BERDASARKAN PENDEKATAN KAPPA - Darmawan Baginda Napitupulu (Jurnal Sistem Informasi, 2014)
Since Inpres No.3 of 2003 about policies and strategies for e-Government development, the Government institution was required to be able to take advantage of the progress of Information and Communication Technology (ICT) in order to improve the efficiency, effectiveness, transparency and accountability of government. The process of transformation towards e-Government was an effort to develop electronic-based government so as to optimize the utilization of ICT in general. Unfortunately, the e-Government developed merely indicate compliance with this policy, because without the quality. Various surveys had shown that Indonesia was still far behind in terms of adoption of e-Government (UNDESA, 2012). This plus the fact that most of the e-Government projects in developing countries, including Indonesia, where the failure rate of failure to achieve up to 85% while the success rate was only 15% (Heeks, 2003). However, there is no doubt there are some areas that successfully implement e-government initiatives. In this study, the authors aimed want to explore what factors determine the success of the implementation of e-Government. The study is descriptive in which the method used is a literature study related to success factors of e-Government implementation. From the results of the validation test based on expert opinion, obtained 15 success factors that must be accommodated to ensure the successful implementation of e-Government. Inter-rater reliability had also been tested with Cohen's Kappa and the approach showed satisfactory results (